Persulfate-promoted oxidative C-N bond coupling of quinoxalinones and: NH -sulfoximines - Ladawan Sumunnee (2019)
© The Royal Society of Chemistry. The persulfate-meditated oxidative C-N bond coupling of the C-H bond of quinoxalinones and the N-H bond of NH-sulfoximines is reported. The reaction proceeds smoothly under transition metal-free conditions and provides good to excellent yields of sulfoximidoyl-functionalized quinoxalinone products under mild conditions. The optimized conditions were found to be suitable for a range of sulfoximine and quinoxalinone substrates. This reaction offers a new and convenient strategy to directly install the sulfoximine moiety into the C3 position of quinoxalinone.